Adenylate Cyclase 1 Links Calcium Signaling to CFTR-Dependent Cytosolic Chloride Elevations in Chick Amacrine Cells - Zhong, Li; Gleason, Evanna L. (Frontiers in Cellular Neuroscience, 2021)
The strength and sign of synapses involving ionotropic GABA and glycine receptors are dependent upon the Cl- gradient. We have shown that nitric oxide (NO) elicits the release of Cl- from internal acidic stores in retinal amacrine cells; temporarily altering the Cl- gradient and the strength or even sign of incoming GABAergic or glycinergic synapses. The underlying mechanism for this effect of NO requires the cystic fibrosis transmembrane regulator (CFTR) but the link between NO and CFTR activation hasn’t been determined. Here, we test the hypothesis that NO-dependent Ca2+ elevations activate the Ca2+-dependent adenylate cyclase 1 (AdC1) leading to activation of protein kinase A (PKA) whose activity is known to open the CFTR channel. Using the reversal potential of GABA-gated currents to monitor cytosolic Cl-, we established the requirement for Ca2+ elevations. Inhibitors of AdC1 suppressed the NO-dependent increases in cytosolic Cl- whereas inhibitors of other AdC subtypes were ineffective suggesting that AdC1 is involved. Inhibition of PKA also suppressed the action of NO. To address the sufficiency of this pathway in linking NO to elevations in cytosolic Cl-, GABA-gated currents were measured under internal and external zero Cl- conditions to isolate the internal Cl- store. Activators of the cAMP pathway were less effective than NO in producing GABA-gated currents. However, coupling the cAMP pathway activators with release of Ca2+ from stores produced GABA-gated currents indistinguishable from those stimulated with NO. Together, these results demonstrate that cytosolic Ca2+ links NO to the activation of CFTR and the elevation of cytosolic Cl-.